We should be given a chance: identifying barriers and enablers from disabled people's employment in the office of the Premier of the Eastern Cape Provincial Government, South Africa - Loyilane, Ndileka Eumera Portia (Division of Disability Studies, 2024)
Disabled people have not been part of the employment processes, especially within government. They have always been encouraged to pursue income-generating projects like sewing, knitting or carpentry. These ventures have resulted in very few disabled people becoming employed in the formal sector and thus being part of the economic growth of the country. The aim of the study was to determine the barriers and enablers to the employment of disabled people in the Provincial Government of the Eastern Cape. The literature review investigates the reasons why disabled people have not been involved in mainstream activities. lt also elaborates on why disabled people have felt the need to advocate for their inclusion in mainstream activities, especially employment, and how this lobby has led to the inclusion of disability in the Constitution, the Bill of Rights (Republic of South Africa, 1996), and further the formulation and adoption of the Employment Equity Act (Department of Labour, 1998). Literature on the barriers to the employment of disabled people is lacking, and most writers refer to the challenges of disabled people who are already employed. Using a qualitative, descriptive research design, a case study approach was utilised to explore the employment experience of disabled people in Office of the Premier (OTP) of the Eastern Cape Provincial Government. Purposive sampling was used to select participants from the OTP, an NGO working in the disability field and members of a Disabled People's Organisation. Data collection included semi-structured interviews and a focus group discussion. The interviews were transcribed, and the concepts that emerged were grouped into categories and then further grouped together to form a theme. Three themes emerged, namely, Paying lip service, Perceptions of disability and Giving disabled people opportunities. The discussion explored the disabling and enabling factors under three subheadings: firstly, creating accessible environments; secondly, transforming recruitment strategies for implementing policies; thirdly, challenging and changing attitudes and myths; and lastly, integrating skills development as an area which plays a central role in ensuring that all the abovementioned factors result in the employment of disabled people. However, the study shows that despite the existence of the legislative framework, disabled people still continue to be unemployed. Recommendations included the suggestion of road shows and sensitisation programmes undertaken to assist in fast tracking the employment of disabled persons in the Office of the Premier of the Eastern Cape Provincial Government.